The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.thromres.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Short-term versus extended anticoagulant treatment for unprovoked venous thromboembolism: A survey on guideline adherence and physicians' considerations

Abstract: Background: In patients with unprovoked venous thromboembolism (VTE), anticoagulant treatment duration should be decided by weighing bleeding risk versus risk of recurrent VTE, considering patient's preference. Because both risks differ between individuals, this recommendation presumably leads to wide variation in clinical management. Objectives: To identify physician's considerations when deciding between short-term and extended anticoagulation and to assess how current guidelines are put to practice. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Two recent, survey-based studies, performed in different geographic context (Australia and Northern Europe), have investigated the physician’s attitude to adhere to the guideline indications. 8,9 Although in both studies most physicians said they followed the guideline indications on the issue (very likely, even our Italian physicians would have given the same answer if asked), both studies showed a considerable variability in VTE management practices, in a way similar to what we found in our study. In particular, the difficulty in assessing the individual patient risk of developing a major bleeding complication during AT was underlined in the study by de Winter et al 9 as well as in the present study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Two recent, survey-based studies, performed in different geographic context (Australia and Northern Europe), have investigated the physician’s attitude to adhere to the guideline indications. 8,9 Although in both studies most physicians said they followed the guideline indications on the issue (very likely, even our Italian physicians would have given the same answer if asked), both studies showed a considerable variability in VTE management practices, in a way similar to what we found in our study. In particular, the difficulty in assessing the individual patient risk of developing a major bleeding complication during AT was underlined in the study by de Winter et al 9 as well as in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Recent reports, with data coming from different countries, confirm a wide variability in the practice of physicians as regards AT duration in management of patients with VTE. 8,9 Although it is relevant to assess to what extent physicians follow the guidelines on this issue, it is also very important to understand how the treating physicians tackle the issue in daily clinical practice; many factors may influence their decision, such as personal experience, confidence in guideline recommendations, and patient characteristics and preferences.…”
Section: Introductionmentioning
confidence: 99%
“…23 Interestingly, this is also what physicians focus most on. 24 In line with previous studies, patients were less concerned with risk of bleeding. 13,23 A possible explanation could be that patients are familiar with VTE, as opposed to bleeding.…”
Section: Relevant Quotessupporting
confidence: 84%
“…Most important reasons for short-term treatment were frequent falls, history of major bleeding, previous bleeding during anticoagulation, the patient's preference and thrombocytopenia. 25 In another international survey from 2020 of clinicians regarding their management of VTE following the initial 3-6 months of anticoagulation, a consensus on long-term management for patients with unprovoked VTE was found. For the remainder, there was a lack of consensus regarding the need for indefinite anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…An online survey investigating physicians' considerations when deciding between short‐term and extended anticoagulation after VTE showed that the most important reasons for extended treatment were, in descending order, the patient's preference, active malignancy, low estimated bleeding risk, history of VTE and haemodynamic instability during previous VTE. Most important reasons for short‐term treatment were frequent falls, history of major bleeding, previous bleeding during anticoagulation, the patient's preference and thrombocytopenia 25 . In another international survey from 2020 of clinicians regarding their management of VTE following the initial 3–6 months of anticoagulation, a consensus on long‐term management for patients with unprovoked VTE was found.…”
Section: Discussionmentioning
confidence: 99%